On Knowing the Specific Aspect of God: Chapter 396 of Muhyi al-Din Ibn al-Arabi's Kitab al-Futuhat al-Makkiyya - Translation and Commentary - Bashier, Salman (Jama'a: an Interdisciplinary Journal of Middle East Studies, 2003)
The article provides a translation and analysis of a short but important chapter from the Futuhat of Muhui al-Din Ibn al-Arabi (1165-1240). This chapter elaborates on the notion of the specific aspect of God, which constitutes the link that connects things in the world with the transcendent truth that brings them to existence and keeps them in existence. The chapter argues that knowledge of the specific aspect of God provides the Realizer with a special capacity by means of which he/she can connect with the transcendent truth, and through that very connection improve his/her judging capacities. It describes the manner of attaining knowledge of the specific aspect and the possibilities that this knowledge opens before the Realizer. Knowledge of the specific aspect of God signifies maturity in mystical wisdom and, contrary to common belief, it does not alienate the Realizer from his/her social and legal settings. Rather, knowing the specific aspect deepens his/her awareness and gives him/her better understanding of these.